The Influence of Digital Talent and Knowledge Sharing on Innovation Capability in Manufacturing Companies - Rinka Aryaastuti; Muhamad Ekhsan (Lentera Ilmu Nusantara, 2026)
This study aims to examine the influence of digital talent and knowledge sharing on innovation capability in manufacturing companies in the Industry 4.0 era. Digital transformation requires manufacturing firms not only to adopt advanced technologies but also to develop employees' digital competencies and establish effective knowledge-sharing systems to support sustainable innovation. This study employs a quantitative approach using a survey method involving employees of manufacturing companies who are directly involved in digital technology utilization and innovation activities. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that digital talent has a positive and significant effect on innovation capability, and knowledge sharing also has a positive and significant effect on innovation capability. These findings highlight that enhancing innovation capability in manufacturing firms relies on the integration of digital talent development and systematic knowledge-sharing practices. This study recommends that manufacturing companies align digital talent development strategies with the establishment of a supportive knowledge-sharing culture and platforms to strengthen innovation-driven competitiveness in the digital era.